EXAMINATION of NURSING STUDENT’S CULTURAL AWARENESS and INTERCULTURAL SENSITIVITY LEVELS : Examination of Nursing Students’ Cultural Awareness And Intercultural Sensitivity Levels - Kheder ABBAS, Noor; ÜNSAL, Ayla (Göbeklitepe Medical Science Journal, 2025)
Nursing students should have a certain level of cultural awareness and intercultural sensitivity while caring for the healthy/patients from different cultures and communicating with their fellow students from different cultures and people they meet in different cultures abroad. The aim of the present study conducted in this direction is to determine the levels of cultural awareness and intercultural sensitivity of nursing students. The descriptive study was conducted on 616 nursing students who are studying at Kırşehir Ahi Evran University, Faculty of Health Sciences, Department of Nursing. The data were collected using the Descriptive Characteristics Form, Intercultural Awareness Scale (ICAS), and Intercultural Sensitivity Scale (ISS). Prior to data collection, institutional approval, ethics committee approval, and student consent were obtained from the institution where the study was conducted. Data were analyzed using counts, percentages, means, standard deviations, Cronbach’s alpha coefficient, Kolmogrow-Smirnow and Shapiro-Wilk tests, independent groups t-test, one-way ANOVA, and Pearson correlation analysis. The level of cultural awareness of the students participating in the study (33.42±4.90) was not very high, but it was above the average level. Although the level of intercultural sensitivity of the students in the present study (84.14±8.00) was not very high, it was found to be above the average level. It was found that there was a positive relationship between students’ cultural awareness and intercultural sensitivity. It was found that as students’ cultural awareness increased, their intercultural sensitivity also increased.